Податок на прибуток підприємств – проблеми контролю за його сплатою з боку держави - Шовкопляс, Тетяна Семенівна (НТУ "ХПІ", 2017)
Метою статті є визначення та удосконалення теоретичних основ і науково- практичних рекомендацій, щодо розкриття сутності контролю за сплатою податку на прибуток підприємств в Україні. Ухилення від сплати податків стало настільки звичним і поширеним явищем, що податок на прибуток підприємств мінімізують не тільки окремі підприємства, а й деякі галузі народного господарства та фінансово-промислові групи. Вагомим джерелом наповнення бюджету залишається податок на прибуток підприємств, проте недосконалість законодавства та низький рівень державного фінансового контролю за діяльністю суб'єктів господарювання призводять до звуження бази оподаткування, зменшення податкових надходжень, нерівномірного та несправедливого податкового навантаження, порушення засад конкуренції, і гальмування розвитку економіки в цілому.

The purpose of the article is to identify and improve the theoretical foundations and scientific and practical recommendations regarding the disclosure of the essence of control over the payment of corporate income tax in Ukraine and the solution of problems that reduce its fiscal efficiency and, as a consequence, require organizational and methodological improvement. Modern economic realities indicate shadow activity in all components of the economic processes of Ukraine. Tax evasion has become so commonplace and widespread that the tax on the profit of enterprises is minimized not only by individual enterprises, but also by certain branches of the national economy and financial and industrial groups. A significants ource of filling the budget remains the corporate profit tax, but the imperfection of legislation and the low level of state control over the activities of economic entities lead to a narrowing of the tax base, a reduction in tax revenues, uneven and unjust tax burden, violation of competition principles, and as a result of the slowdown in the development of the economy as a whole.
Corporate income tax – the problem of controlling its payment by the state
Keywords: фінансова сфера; національна економіка; податки; державний фінансовий контроль; financial sphere; national economy; taxes; profit tax